IDNLearn.com: Where your questions meet expert answers and community support. Ask anything and receive prompt, well-informed answers from our community of knowledgeable experts.

Given the function defined in the table below, find the average rate of change, in simplest form, of the function over the interval [tex]$12 \leq x \leq 36$[/tex].

\begin{tabular}{|c|c|}
\hline
[tex]$x$[/tex] & [tex]$f(x)$[/tex] \\
\hline
0 & 37 \\
\hline
12 & 34 \\
\hline
24 & 31 \\
\hline
36 & 28 \\
\hline
48 & 25 \\
\hline
60 & 22 \\
\hline
\end{tabular}


Sagot :

To determine the average rate of change of the function over the interval [tex]\(12 \leq x \leq 36\)[/tex], we need to follow these steps:

1. Identify the interval boundaries and corresponding function values:
- The interval given is [tex]\([12, 36]\)[/tex].
- For [tex]\(x = 12\)[/tex]: [tex]\(f(12) = 34\)[/tex].
- For [tex]\(x = 36\)[/tex]: [tex]\(f(36) = 28\)[/tex].

2. Apply the formula for the average rate of change:
- The average rate of change of a function [tex]\(f\)[/tex] over the interval [tex]\([x_1, x_2]\)[/tex] is given by:
[tex]\[ \text{Average rate of change} = \frac{f(x_2) - f(x_1)}{x_2 - x_1} \][/tex]

3. Substitute the values into the formula:
- Here, [tex]\(x_1 = 12\)[/tex], [tex]\(x_2 = 36\)[/tex], [tex]\(f(x_1) = f(12) = 34\)[/tex], and [tex]\(f(x_2) = f(36) = 28\)[/tex].
- Substitute these into the formula:
[tex]\[ \text{Average rate of change} = \frac{f(36) - f(12)}{36 - 12} = \frac{28 - 34}{36 - 12} \][/tex]

4. Simplify the expression:
- First, calculate the difference in the numerator:
[tex]\[ 28 - 34 = -6 \][/tex]
- Next, calculate the difference in the denominator:
[tex]\[ 36 - 12 = 24 \][/tex]
- Now, divide the results:
[tex]\[ \frac{-6}{24} = -0.25 \][/tex]

Therefore, the average rate of change of the function over the interval [tex]\(12 \leq x \leq 36\)[/tex] is [tex]\(-0.25\)[/tex].